Effect of the Wall-Back Inclination Angle on the Inertial Loading Distribution along Gravity-Retaining Walls: An Experimental Study on the Shaking Table Test. (23rd December 2022) - Ma, Shuzhi; Jia, Hongbiao; Liu, Xiaolang
Abstract : The gravity-retaining wall is a common retaining structure in geotechnical engineering. The inertial load acting on the retaining wall itself (the horizontal seismic action) under earthquake conditions is one of the major loadings to be elaborately considered for the design of gravity-retaining walls. The horizontal seismic action of the retaining walls under seismic loading is dominated by the combination of the mass distribution of the wall body and the acceleration distribution along wall height. The mass distribution can be calculated by the wall geometry and density of the wall body. By contrast, due to the whipping effect, horizontal seismic acceleration along wall height often shows obvious amplification in relation to ground acceleration. Such a distribution of acceleration amplification is of great importance to comprehend the safe design of retaining walls. Nonvertical retaining walls, such as inclined and reclined retaining walls, are often used in practical engineering, and their dynamic responses under seismic actions will be different from those of vertical walls. This paper focused on the examination of the influence of the wall-back inclination angle of retaining walls on the dynamic acceleration distribution along wall height due to seismic actions. Dynamic responses of vertical, inclined, and reclined gravity retaining walls under various earthquake loads were tested on a shaking table system. Seismic acceleration time-history curves were recorded under different seismic waves and intensities. The influence of the wall-back inclination angle of retaining walls on the seismic effect was thus analyzed. The tested results showed that the wall-back inclination angle of retaining walls has a significant influence on the seismic dynamic response. The amplification coefficients of peak acceleration of the gravity retaining wall follow the order of the reclined type > the vertical type > the inclined type. Based on the experimental results, the amplification coefficient of peak acceleration was statistically analyzed under the commonly used risk level in engineering seismic design. A formula for the calculation of the horizontal earthquake action distribution coefficient along wall height was proposed involving the effect of the wall-back inclination angle, which might improve the existing calculation method of retaining wall design. The results of this work would guide the earthquake resistance dynamic design of retaining walls.